Pengaruh Disiplin Kerja, dan Motivasi Kerja terhadap Kinerja Karyawan di UD. FF Tirta, Jakarta Timur - Leksono, Ari Wahyu; Abdillah, Agus; Anco, Anco (FOCUS, 2023)
At this time the business of bottled drinking water distributors, especially those engaged in the field of Aqua Galon distributors, is indeed experiencing quite significant increase. This increase was balanced with the increasing number of competitors which resulted in a decrease in sales turnover in the field, so that this situation made the business owner have to play strategies in order to increase employee performance, namely by implementing work discipline and providing work motivation to their employees. The purpose of this study is to find out how much the influence of work discipline and work motivation on employee performance in UD. FF Tirta, East Jakarta. The population used was 30 respondents and used saturated sampling. The methods used are validity tests, reliability tests, classical assumptions tests, determination coefficient tests, multiple linear regression tests, and statistical tests. The scale used is a Likert scale. By using SPSS 26 software, so that the results of the multiple linear regression equation y = ? + ?1x1 + ?2x2 + ? = 16,253 - 0.038 - 0.20. The results of partial testing for work discipline variables have a t count value of -3,043 with a significance value of 0.013 <0.05 while for the work motivation variable has a t count value of -10.035 with a significance value of 0.020 <0.05. So that the two variables are the decision to refuse H0. So judging from the decision, the two variables each have partial influence on employee performance variables. From the results of the coefficient of determination, the adjusted R square value is valued at 0.796 or 79.6% means that the independent variables used in the model are work discipline variables (X1), and work motivation (X2) are able to explain 79.6% of the dependent variable, namely employee performance ( Y), while the remaining 20.4% is explained by other factors.